PERSEPSI SISWA TENTANG KOMPETENSI SOSIAL GURU DI SEKOLAH MENEGAH ATAS NEGERI 8 PADANG - Fajri Rahmadeli (Jurnal Bahana Manajemen Pendidikan, 2017)
The study aims to determine how the student’s perception of Social Competence of Teachers at the senior   high school (SMA) 8 Padang views of skills in communication with students using communication and information technology, interact effectively with student, teachers and parent’s students andinteract politely with people.This is a descriptive study, the study population was all students of SMA Negeri 8 Pariaman with a sample of 791 people drawn from 10% of the population using  stratified random sampling techniques. Data collection tools used were Linkert Scale questionnaire. The data were analyzed with the average formula (mean). The results showed student's perception of social competence of teachers at the senior high school (SMA) 8 Padang views of skills in communication, using communication and information technology, interact effectively, in the category able with an average score of 4,16. Keywords: Social Competence of Teachers